An overview of Human Papillomavirus (HPV) as an etiological factor of the anal cancer. Issue 1 (January 2019) - Krzowska-Firych, Joanna; Lucas, Georgia; Lucas, Christiana; Lucas, Nicholas; Pietrzyk, Łukasz
Abstract: Human papillomavirus (HPV) is a DNA tumour virus that is the primary cause of sexually transmitted infections (STIs). The direct connection between HPV and cervical cancer was discovered in 1980, however, many physicians and the general public are still oblivious to the association of HPV and anal cancer; most individuals find out about this relationship after a confirmed diagnosis, and therefore, it is important to raise awareness about HPV as an etiological agent in anal cancer. There is a quadrivalent vaccine available, which prevents an individual from being infected with HPV, thus anal cancer is mainly a preventable cancer when caused by HPV, and ultimately, preventing cancer is better than curing cancer, especially when there is no definite cure.This article aims to review the microbiology, pathophysiology, epidemiology, clinical presentation, diagnostic evaluation, prophylaxis and treatment options for HPV as an etiology agent in anal cancers in light of recent literature.